2015
DOI: 10.1177/0194599815607841
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, Specificity, and Posttest Probability of Parotid Fine‐Needle Aspiration

Abstract: Objectives (1) To analyze the sensitivity and specificity of fine-needle aspiration (FNA) in distinguishing benign from malignant parotid disease. (2) To determine the anticipated posttest probability of malignancy and probability of non-diagnostic and indeterminate cytology with parotid FNA. Data Sources Independently corroborated computerized searches of PubMed, Embase, and Cochrane Central Register were performed. These were supplemented with manual searches and input from content experts. Review Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
133
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 79 publications
16
133
2
7
Order By: Relevance
“…In our study, we found a sensitivity of 82.4% and specificity of 90.4% for detecting malignancy. The higher rate of specificity compared to sensitivity is consistent with the findings of prior studies . This indicates that a positive result on FNA is highly likely to be truly positive for malignancy, and thus can be reliably used to guide management.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we found a sensitivity of 82.4% and specificity of 90.4% for detecting malignancy. The higher rate of specificity compared to sensitivity is consistent with the findings of prior studies . This indicates that a positive result on FNA is highly likely to be truly positive for malignancy, and thus can be reliably used to guide management.…”
Section: Discussionsupporting
confidence: 86%
“…Prior studies have reported a wide range of results on accuracy of FNA for detecting malignancy, with sensitivities ranging from 33% to 100% and specificities ranging from 67% to 100% . A 2016 systematic review by Liu et al reported a pooled analysis of 63 studies including 5,647 patients, and demonstrated sensitivity of 88.2% and specificity of 99.5% . In our study, we found a sensitivity of 82.4% and specificity of 90.4% for detecting malignancy.…”
Section: Discussionsupporting
confidence: 58%
“…A more recent meta-analysis has shown similar estimates for the ability of parotid FNA to differentiate benign versus malignant (sensitivity 78% and specificity 98%). 3 Although both of these studies show good sensitivity and specificity there is considerable heterogeneity among individual studies ranging from 0% to 100% for sensitivity and 67% to 100% for specificity. 2, 3 …”
Section: Introductionmentioning
confidence: 99%
“…The most common location, as reported in the literature is on the parotid gland. [1][2][3] The salivary gland tumours are usually encountered clinical problems. In the literature, there is inconstancy between the time the tumour is first noticed by the patient and when it is presented to the physician.…”
Section: Introductionmentioning
confidence: 99%
“…Also, diagnostic tests seem to be very significant in management of parotid neoplasms. 1 Three diagnostic tests are recommended to definitively diagnose a tumour as benign or malignancy. The first diagnostic test is fine-needle aspiration biopsy (FNAB).…”
Section: Introductionmentioning
confidence: 99%